2021
DOI: 10.1007/s12035-021-02625-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile in Plasma AND CSF of LEVODOPA-induced Dyskinesia in Parkinson’s Disease: Focus on Neuroinflammation

Abstract: The existence of few biomarkers and the lack of a better understanding of the pathophysiology of levodopa-induced dyskinesia (LID) in Parkinson's disease (PD) require new approaches, as the metabolomic analysis, for discoveries. We aimed to identify a metabolic profile associated with LID in patients with PD in an original cohort and to confirm the results in an external cohort (BioFIND). In the original cohort, plasma and CSF were collected from 20 healthy controls, 23 patients with PD without LID, and 24 pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Metabolomic analysis. Untargeted metabolomic data were analyzed as previously described by our group (25,26). Briefly, metabolite was extracted, and samples were transferred to autosampler vials for LC-MS analysis using a TripleTOF5600 1 mass spectrometer (AB SCIEX, Foster City, CA) coupled to an ultra-HPLC system (Nexera ×2; Shimadzu, Kyoto, Japan).…”
Section: Hplc Tandem Mass Spectrometry (Lc-ms/ms)mentioning
confidence: 99%
“…Metabolomic analysis. Untargeted metabolomic data were analyzed as previously described by our group (25,26). Briefly, metabolite was extracted, and samples were transferred to autosampler vials for LC-MS analysis using a TripleTOF5600 1 mass spectrometer (AB SCIEX, Foster City, CA) coupled to an ultra-HPLC system (Nexera ×2; Shimadzu, Kyoto, Japan).…”
Section: Hplc Tandem Mass Spectrometry (Lc-ms/ms)mentioning
confidence: 99%
“…15 Neuroinflammation is thought to be involved in the pathogenesis of levodopa-induced dyskinesia. 16,17 The Parkinson's disease group treated with a daily 12 mg/ kg of levodopa for 15 days developed dyskinetic movement. On western blotting, this group further showed a significant increase of both D1R and D2R are responsible for levodopa-induced dyskinesia.…”
Section: Amphiregulin Is Highly Expressed In the Levodopa-induced Dys...mentioning
confidence: 99%
“…Metabolomics has attracted attention in recent years, revealing multiple novel metabolic pathways linked to the pathogenesis of PD. Several studies demonstrated altered metabolic profiles in PD, PD subgroups, APS and other neurological conditions [ 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. By utilizing machine learning algorithms, 14 CSF metabolites were identified that enabled distinguishing early PD from controls with high accuracy [ 104 ].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Concerning PD medication-related sequelae, dysregulations in bile acid biosynthesis and glycosphingolipid/glycerophospholipid metabolism were able to distinguish PD patients suffering levodopa-induced dyskinesia (LID) from PD without LID and controls, pointing towards a further association between dysregulated lipid metabolism and neuroinflammation [ 98 ]. Intriguingly, an altered glycosphingolipid metabolic pathway was strongly associated with the severity of dyskinetic movements.…”
Section: Metabolomicsmentioning
confidence: 99%